Application of optimal control in Vertical Weight Stabilizer (VWS) system for actual ship - Ramli, Muhammad Zahir; Hirakawa, Yoshiaki (IIUM Press, International Islamic University Malaysia, 2017)
Improvement of stability has been going for decades. Anti-rolling system like bilge keel, anti-rolling tank, and weight stabilizer, those basic ideas were first proposed by researchers in the period of latter half of 19th century. While on the other hand, fin stabilizer was invented around 1920`s. Some of the ideas remain undeveloped for years while others turned out to be a successful system in years to come.